Genealogías críticas para pensar “Nuestra América”. Fronteras, migraciones y desplazamientos teóricos - López, Irene (2020)
Critical thinking in Latin America had a sustained development over the 20th century which has left methodological perspectives, categories and approaches of fundamental importance for the study and understanding of cultural phenomena, such as literary, artistic and musical expressions. In that path, Antonio Cornejo Polar's contributions, with the notions of “heterogeneity”, “contradictory totality”, and “migrant subject” are still one of the most productive and powerful inputs to account for cultural productions and its questions.Critical and theoretical thinking do not stay out of these complex and tense modes of production that Cornejo Polar pointed out as peculiar to the cultural production in Latin America. This work seeks to consider the effectiveness and applicability of this critical course emphasizing the potential and productivity of thought across frontiers, either cultural, discipline and category-related. On that note, conceptual borrowings, displacements and migrations show its fruitfulness in the theoretical and critical framework which, from a situated thought, contributes to the study of complex production processes in our contexts.